STRATEGI PENGEMBANGAN USAHA GULA AREN DI DESA RAMBAH TENGAH BARAT KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Sri Rahmi Azhari; Sri Kartikowati; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstracts : Business owners of palm sugar in Rambah Tengah Barat Villagehas a limited to develop their businesses due to resources organization problems,production and marketing. On the other hand, the palm sugar has high economisvalues and able potentially increase their income. The purpose of this reseach is toanalyse the alternatives strategy in developing palm sugar production based onSWOT analysis. The population are all palm sugar business owners in the RambahTengah Barat Village amounted of 30 people and samples are taken five businessowners. Data is collected trough documentation study, questionnaires and interviewtechnique. Data is then, analyzed by descriptive qualitative based on SWOT analysis.This result of the research is seven alternatives of business development strategies thathave been prioritized. The seven alternative strategies are: (1) its partnership ties withbusiness development agencies; 1) its partnership ties with business developmentagencies; (2) the establishment of business partnerships with other parties; (3)providing integrated marketing center for the area of industrial products; (4)development of microfinance institutions; (5) establishment of agro-industryinformation service center; (6) availability relevant instructors; (7) productdiversification.Keywords: Business Development Strategy, palm sugar, SWOT Analysis